THE EFFECTS OF ADDING DIFFERENT CARBON ON GROWTH AND SURVIVAL RATE OF TILAPIA FRY (Oreochromis niloticus) - Firmansyah, Rodhi; Arsanti, Arsanti; Panggabean, Nabilah Hanum; Nasution, Muhaimin Umri (Asian Journal of Aquatic Sciences, 2020)
The Utilization of appropriate carbon sources will have a good impact on the application of biofloc technology in aquaculture. This study aims to effects of adding different carbon on growth and survival rate of tilapia fry (Oreochromis niloticus). The fries were kept by the densities 30 fries/tank. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments were the addition of different carbon sources on the media biofloc: A (tapioca), B (molasses), C (wheat flour), and K (control). The results showed that the absolute rate of weight and length were found on the treatment of molasses (B) was 5.84 grams, 3.5 cm and significantly different from the other treatments (P <0.05). While the highest survival rate is 83.33% at molasses (B). The mean temperature at 28.1 to 30.00 oC, the DO from 5.00 to 7.60 mg / L and pH 5.00-7.20.